Syntax Acquisition in Children: Developmental Patterns and Cognitive Processes - Ellisa Indriyani Putri Handayani; Agus Hari Wibowo (Universitas Cokroaminoto Palopo, 2024)
This research looks into the complicated steps kids take to learn grammar, focusing on how socioeconomic status (SES), being bilingual, and getting help early on affect this process. The introduction shows how important it is to understand how syntax develops in order to make educational practices more effective and open to everyone. To test syntactic learning, the method uses a mix of experimental, quasi-experimental, and naturalistic observation methods. Structured experiments and longitudinal studies are two important ways to study language development over time. Structured experiments control variables and measure syntactic knowledge and production. The results show that SES has a big effect on how syntax develops, with environments with higher SES giving stronger linguistic input. When learning grammar, being bilingual can be both hard and helpful, depending on how old you are when you start learning and how often you use the language. Children who are at risk of language delays gain a lot from early interventions, especially those that focus on improving phonological awareness and vocabulary. The talk makes it clear that early and focused interventions are needed to reduce differences in outcomes based on socioeconomic status and improve the development of syntax in both bilingual and monolingual children. The results support using research-based linguistic knowledge in the classroom to help all students do better with language, but especially those who have developmental language problems.